Effects of replacing concentrate by irrigated or rain fed corn hay (pre-mature) on the performance of Awassi lambs - Khazaal K.; Houcheymi K.; Haj Yosef A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The ability of premature irrigated (IRR) or Rainfed corn as hay to gradually replace concentrate and barley straw was investigated. 21 Awassi lambs of similar weight (32 kg±3.96) were randomly divided into 3 groups (3 males and 4 females). Feeding was adjusted according to live body weight (LBW) at 3%. The control group was always fed a typical fattening diet composed of 60% concentrates (18% CP; 12MJ ME) and 40% barley straw. At the 1st stage (14 days) and 2nd stage (21 days), 30% and 40% of the concentrate was replaced by IRR or rainfed corn hay. During the 3rd stage (21 days) the concentrate and barley straw were totally replaced by ad libitum feeding of either IRRI or Rainfed corn hay. The DM yield as hay was 53625 kg DM/ha from IRR and 21710 kg DM/ha from Rainfed corn. LBWG was similar to the Control group during the 1st and 2nd stage. However, when corn hay was fed ad libitum, LBWG was higher but not significantly (P>0.05) for the IRR (197 g/day) and the Rainfed (245 g/day) as compared to control (170 g/day). Corn hay can partially or totally replace concentrate. The cost of feeding corn hay was also lower than concentrate and barley straw. The production, storage and feeding of corn hay was easy to apply by small farmers as compared to silage and reduced the cost of feeding and can improve the health status of animals.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)